2009
DOI: 10.1039/b821264c
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence, electrochemistry and host–guest properties of dinuclear platinum(ii) terpyridyl complexes of sulfur-containing bridging ligands

Abstract: A series of dinuclear platinum(ii) terpyridyl and terpyridyl-crown complexes with 2,2-dicyano-1,1-ethylenedithiolate (i-mnt), 1,3-benzenedithiolate (SC(6)H(4)S-1,3) and N,N-diethyldithiocarbamate (dtc) bridging ligands have been synthesized and characterized. Their photophysical and electrochemical properties, together with that of the related mononuclear platinum(ii) terpyridyl-crown complex and its crown-free analogue, have been studied. The ion-binding properties of the terpyridyl-crown complexes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…A slight variation in Pt–S bond distances was noticed in all the three structures: 2.37−2.39 Å for for 4a-I , 2.36–2.37 Å for 4b-II , and 2.37–2.39 Å for 4c-III . These distances match well with the Pt–S bond distances in analogous complex [Pt 2 (μ- o -SC 6 H 4 (CF 3 )) 2 (dppe) 2 ]­(OTf) 2 (2.38 Å) but are longer than those in in [Pt 2 (dppf) 2 (C 8 H 8 NS)]­(BF 4 ) (2.34 Å) and [Pt 2 (terpyridine) 2 (1,3-SC 6 H 4 S)] 2 (PF 6 ) 2 (2.31 Å) . The bite angles (101–102°) for 4a-I and 4b-II agree well with those of complexes [Pt­(Xantphos)­Cl 2 ] (101°) and [Pt 3 (Xantphos) 2 {(SeCH 2 ) 2 C­(CH 2 OH) 2 }]­Cl 2 ] (101°) but are smaller than that of the allyl complex [Pt­(η 3 -allyl)­(Xantphos)]­(OTf) (107°), whereas the bite angles 98–99° for 3c-III are shorter than the usual values for a wide bite angle (>101°) in Xantphos complexes.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A slight variation in Pt–S bond distances was noticed in all the three structures: 2.37−2.39 Å for for 4a-I , 2.36–2.37 Å for 4b-II , and 2.37–2.39 Å for 4c-III . These distances match well with the Pt–S bond distances in analogous complex [Pt 2 (μ- o -SC 6 H 4 (CF 3 )) 2 (dppe) 2 ]­(OTf) 2 (2.38 Å) but are longer than those in in [Pt 2 (dppf) 2 (C 8 H 8 NS)]­(BF 4 ) (2.34 Å) and [Pt 2 (terpyridine) 2 (1,3-SC 6 H 4 S)] 2 (PF 6 ) 2 (2.31 Å) . The bite angles (101–102°) for 4a-I and 4b-II agree well with those of complexes [Pt­(Xantphos)­Cl 2 ] (101°) and [Pt 3 (Xantphos) 2 {(SeCH 2 ) 2 C­(CH 2 OH) 2 }]­Cl 2 ] (101°) but are smaller than that of the allyl complex [Pt­(η 3 -allyl)­(Xantphos)]­(OTf) (107°), whereas the bite angles 98–99° for 3c-III are shorter than the usual values for a wide bite angle (>101°) in Xantphos complexes.…”
Section: Resultssupporting
confidence: 78%
“…However, the calculations showed that the similar complex [M′ 2 (Xantphos) 2 (1,3-SC 6 H 4 S)] 2 (OTf) 4 ( II′ ) with phenylene-1,3-dithiolate and the possibility of another neutral complex [M′ 2 (Xantphos) 2 (SC 6 H 4 S) 2 ] ( IV ) are inherently unstable, probably due to the overcrowding of ligands (Scheme S1). The reported platinum complex [Pt 2 (terpyridine) 2 (1,3-SC 6 H 4 S)]­(PF 6 ) 2 exist as linear dimeric complex …”
Section: Resultsmentioning
confidence: 99%
“…For example the two ppy ligands of 3a give two different sets of signals with the chemical shifts of the protons of the overlapping ppy being 0.4–0.9 ppm lower than that of the nonoverlapping one. Most of the protons of the terpy do not overlap with L, but the H 13 , which is covered significantly by L, shows an upfield-shifted signal, that is, the H 13 signals of 3a (δ 8.34) and 4a (δ 8.39) are lower than that of the corresponding proton in similar complexes such as [Pt 2 (terpy) 2 ­(μ-SMe)]­(ClO 4 ) 3 (δ 9.7), and [Pt­(terpy)­(SCH 2 CH 2 OH)]­(PF 6 ) (δ 9.16) . The results indicate that the rings remain overlapped in the solutions and probably have the same conformations as depicted in the X-ray crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…Bimetallic complexes exhibit unique structural and optical properties that differ from mononuclear metal center complexes, as facilitated by the presence of the metal–metal bond. With small bond lengths, metal-to-ligand charge transfer (MLCT) is induced, but with longer bonds metal–metal-to-ligand charge transfer (MMLCT) occurs. Platinum–platinum dimers showcase such phenomena across a broad range of complex structures …”
Section: Introductionmentioning
confidence: 99%